Pengaruh Pendekatan Kontekstual (Contextual Teaching and Learning) pada Anak Tunanetra di SLB ABD Negeri Kedungkandang, Kota Malang - Mauliddin, Muhammad Arif; Cahyono, Ilham Dwi; M, Mardatillah; Lazuardi, Muhammad Alfan; Y, Yana; Alfina, Nur Aulia; Ummah, Umi Safiul; Harisandi, I GST. Ngurah Putu (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This study aims to analyze the influence of the contextual teaching and learning (CTL) approach on the learning process of visually impaired children at SLB ABD Negeri Kedungkandang, Malang City. The CTL approach connects the learning material with real situations, so that students can understand concepts in depth and applicatively. The research method used is quantitative descriptive research with data collection techniques through observation, interviews, and documentation. The results of the study show that the application of the CTL approach has a positive impact on the understanding of visually impaired students, their motivation to learn, and their ability to relate lessons to daily life. Visually impaired students who engage in contextual-based learning show significant improvements in cognitive, affective, and psychomotor skills. Supporting factors for the successful implementation of CTL include the role of teachers as facilitators, the use of learning media that suit the needs of visually impaired students, and an inclusive learning environment.